The Association between Adherence to Oral Antihyperglycemic Agent and HbA1c Level - Soraya, Indana Ayu; Sauriasari, Rani; Prawiroharjo, Pukovisa; Risni, Hindun Wilda (UI Scholars Hub, 2022)
Adherence to taking medication is essential for patients with chronic diseases such as Type 2 Diabetes Mellitus (T2DM). There have been many studies about the association between medication adherence and HbA1c levels, but few have used Adherence Refills and Medications Scale (ARMS) questionnaire and Proportion of Days Covered (PDC) method to measure adherence in Indonesian population. The aim of this study were to assess the association of medication adherence to HbA1c levels and compare two methods of adherence measurements. This research was conducted at Pasar Minggu Public Health Center, Jakarta using a cross-sectional design. The adherence assessment was conducted using a validated Indonesian version of the ARMS questionnaire and compared to the pharmacy refill adherence method using the PDC calculation. One hundred twenty-seven T2DM patients (75.6% female) with mean age of 58.69 years were recruited. The proportion of adhere patients as measured by ARMS was only 39.4% (50/127). Meanwhile, the proportion of adhere patients as measured by PDC was 77.2% (98/127). Adherence by both measurement showed significant associations with HbA1c <7% (ARMS, OR 4.000 (95% CI 1.705 – 9.386), p = 0.002; PDC, OR 5.674 (95% CI 1.266 – 25.438), p = 0.024). After controlled by covariates, the result remained significant (ARMS, aOR 4.281 (95% CI 1.785 – 10.267, p = 0.001; PDC, aOR 5.83 (95% CI 1.287 – 26.405), p = 0.022). Adherence and HbA1c levels was significantly associated even after controlling covariates. ARMS and PDC generated different proportions of adhere patients and may indicate the need of combining the two methods in measuring adherence.